2020
DOI: 10.1111/myc.13073
|View full text |Cite
|
Sign up to set email alerts
|

Species distribution of the main aetiologic agents causing skin dermatophytosis in Colombian patients: A 23‐year experience at a Mycological Reference Center

Abstract: | INTRODUC TI ONDermatophyte infections are a type of infection produced by different groups of pathogenic fungi for humans and some animals. These fungi can invade keratinised structures such as the stratum corneum, hair and nails. 1,2 Dermatophytosis is among the most frequently diagnosed skin infections worldwide. 3,4 It is produced by dermatophytes that can digest and use keratin as a substrate, comprising seven genera with four being recognised as affecting human beings, namely, Trichophyton, Microsporum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The most frequently isolated etiological agents in Colombia are T. rubrum , followed by T. mentagrophytes species complex , and E. floccosum . The most common clinical forms are tinea pedis and tinea corporis [22].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently isolated etiological agents in Colombia are T. rubrum , followed by T. mentagrophytes species complex , and E. floccosum . The most common clinical forms are tinea pedis and tinea corporis [22].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, a number of publications from different geographic areas focusing on dermatophytes' species epidemiology reported data from Eastern Europe (Colosi et al, 2020) and the Balkan (Otašević et al, 2019;Sakkas et al, 2020), from the Middle East (Ozkutuk et al, 2007;Armon et al, 2020), Africa (Coulibaly et al, 2018), South East Asia (Do et al, 2017), and South America (Silva-Rocha et al, 2017;Carrascal-Correa et al, 2020).…”
Section: Incidence and Dermatophyte Species Distribution In Different Geographic/climatic Regionsmentioning
confidence: 99%
“…The prevalence and causative agents of tinea faciei vary across regions. The reported isolation rates range from 0.4% to 4.2% in various parts of the world [ 16 , 17 , 18 , 19 , 20 , 21 , 26 , 36 , 37 , 38 , 39 , 40 , 58 , 59 ], with more than 50% of cases observed in patients younger than 12 years of age [ 37 , 60 ]. In Europe, a study conducted in Portugal identified M. audouinii , T. soudanense , and T. rubrum as the main pathogenic agents [ 60 ].…”
Section: Body Sites Dermatophyte Species and Their Geographical Distr...mentioning
confidence: 99%
“…In Africa, the estimated prevalence ranges from 2% to 41% [ 3 ]. In other regions, the prevalence of tinea corporis among isolated dermatophytes is estimated to be between 2.8% and 30.3% ( Table 2 ) [ 16 , 17 , 18 , 19 , 20 , 21 , 26 , 36 , 37 , 38 , 39 , 40 , 58 , 59 ]. Notably, in India, there has been a shift in prevalence over the past two decades, with T. mentagrophytes emerging as a replacement for T. rubrum [ 27 , 68 ].…”
Section: Body Sites Dermatophyte Species and Their Geographical Distr...mentioning
confidence: 99%